Implementasi Digital Signage Sebagai Media Informasi Dilengkapi Sensor Pir Berbasis Microprocessor Raspberry Pi - Rosman, Edwar; G, Katrina Flomina (JURTEII: Jurnal Teknologi Informasi, 2023)
Abstract - In this modern era, digital technology is rapidly advancing, and the delivery of information through conventional media is being abandoned, replaced by the use of electronic media. One of the digital technologies currently emerging as an information medium is Digital Signage. Digital Signage is a digital content management application programmed to effectively display information or messages. The creation of Digital Signage, which components consist of a server, web, Liquid Crystal Display (LCD) monitor, Raspberry Pi Microprocessor, Light Emitting Diode (LED), Speaker, and software, equipped with a Passive Infrared Receiver (PIR) sensor, makes it optimal in conveying information. This Digital Signage is also designed to support the automation of information delivery to audiences in its vicinity.